Population Pharmacokinetics of Higher-Dose Mizoribine in Healthy Male Volunteers - Suzuki, Tadakiyo; Honda, Mutsuko; Itoh, Hiromichi; Hashimoto, Yukiya (Biological & Pharmaceutical Bulletin, 2006)
The population pharmacokinetic parameters of mizoribine in healthy subjects were estimated using a nonlinear mixed effects model (NONMEM) program. Pharmacokinetic data for population analysis were obtained in the previous study, in which 24 healthy Caucasian male subjects participated in a single-dose (3, 6, 9, 12 mg/kg) study, and 12 subjects participated in a multiple-dose (6, 12 mg/kg/d) study. The mean value of the absorption lag time, absorption rate constant (KA), and apparent distribution volume (V/F) was estimated to be 0.349 h, 0.869 h−1, and 0.834 l/kg, respectively. Oral clearance (CL/F) was modeled with creatinine clearance (CLcr), and the mean value was estimated to be 1.93·CLcr l/h. In addition, pharmacokinetic parameters in individual 36 subjects were obtained from population estimates according to Bayes' theorem. Pharmacokinetic parameters (KA, V/F, and CL/F) in the single-dose study were almost constant at a dose range of 3—12 mg/kg, and were similar to those in the multiple-dose study. These findings indicated that the pharmacokinetics of mizoribine is well described by a simple one-compartment model with first-order absorption.